Pengaruh Penambahan Cangkang Kemiri Terhadap Karakteristik Komposit Poliuretan - Silvia Silvia; Rochmi Widjajanti; Ida Nur Apriani (Program Studi Teknik Kimia, Universitas Pamulang, 2023)
Composite was made to increase the durability of the material. In this study, 5 variations were carried out on candlenut shell powder, 18, 22, 26, 30, 34 grams. The study aims to know the effect of adding candlenut shell powder in polyurethane composite. The material characterization carried out using Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR), Universal Testing Machine (UTM), and thermal properties testing using Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). The addition of candlenut shells affects the characteristics of the polyurethane composite. Composite looks uniform on the surface and it has the same functional groups as pure polyurethane like N-H, C-H alkanes and C=O. For tensile strength test, it was found that PU-26 had the best tensile strength of 10,531 MPa. Based on the DSC test results, it was found that PU-30 had the highest melting temperature of 276.4â„ƒ with an enthalpy/âˆ†H of 8.058 (J/g).